Rhodopsin gene copies in Japanese eel originated in a teleost-specific genome duplication - Yoji Nakamura; Motoshige Yasuike; Miyuki Mekuchi; Yuki Iwasaki; Nobuhiko Ojima; Atushi Fujiwara; Seinen Chow; Kenji Saitoh (Zoological Letters, 2017)
Abstract Background Gene duplication is considered important to increasing the genetic diversity in animals. In fish, visual pigment genes are often independently duplicated, and the evolutionary significance of such duplications has long been of interest. Eels have two rhodopsin genes (rho), one of which (freshwater type, fw-rho) functions in freshwater and the other (deep-sea type, ds-rho) in marine environments. Hence, switching of rho expression in retinal cells is tightly linked with eels’ unique life cycle, in which they migrate from rivers or lakes to the sea. These rho genes are apparently paralogous, but the timing of their duplication is unclear due to the deep-branching phylogeny. The aim of the present study is to elucidate the evolutionary origin of the two rho copies in eels using comparative genomics methods. Results In the present study, we sequenced the genome of Japanese eel Anguilla japonica and reconstructed two regions containing rho by de novo assembly. We found a single corresponding region in a non-teleostean primitive ray-finned fish (spotted gar) and two regions in a primitive teleost (Asian arowana). The order of ds-rho and the neighboring genes was highly conserved among the three species. With respect to fw-rho, which was lost in Asian arowana, the neighboring genes were also syntenic between Japanese eel and Asian arowana. In particular, the pattern of gene losses in ds-rho and fw-rho regions was the same as that in Asian arowana, and no discrepancy was found in any of the teleost genomes examined. Phylogenetic analysis supports mutual monophyly of these two teleostean synteny groups, which correspond to the ds-rho and fw-rho regions. Conclusions Syntenic and phylogenetic analyses suggest that the duplication of rhodopsin gene in Japanese eel predated the divergence of eel (Elopomorpha) and arowana (Osteoglossomorpha). Thus, based on the principle of parsimony, it is most likely that the rhodopsin paralogs were generated through a whole genome duplication in the ancestor of teleosts, and have remained till the present in eels with distinct functional roles. Our result indicates, for the first time, that teleost-specific genome duplication may have contributed to a gene innovation involved in eel-specific migratory life cycle.